Entrepreneurial characteristics associated with the performance of micro, small and medium TBFs of the ICT sector in Ribeirão Preto - Eliza Maria da Cunha Bomfim; Ana Lúcia Vitale Torkomian (GEPROS: Gestão da Produção, Operações e Sistemas, 2017)
The importance of entrepreneurship in a society is widely known due to its influence on the growth and development of countries. Technology-based companies, such as those of the Information and Communication Technology sector, are an important source of new jobs and provide a crucial stimulus for national economies. For these companies, rapid growth is usually an indication of the wide acceptance of their products or services on the market. However, even after several years of operation, many TBCs still have difficulties in improving their performance. In this context, this paper aims to associate the entrepreneurial characteristics of six owner-managers of micro, small and medium enterprises in the ICT sector in the city of Ribeirão Preto – SP, seeking to draw a parallel between the performance of their businesses. From the questionnaires applied, the existence of entrepreneurial traits on a larger scale among the most successful entrepreneurs was verified, confirming, for these cases, the literary evidence which stipulates that this is an important factor for better performance of organizations.